Updated catalog of the vascular plants of Isla del Coco National Park - Estrada-Chavarría, Armando; Sánchez-González, Joaquín; Rodríguez-González, Alexander (Revista de Biología Tropical, 2020)
Introduction: The flora of Isla del Coco has been the subject of various collection studies and publications efforts for more than 300 years. During these years 263 species were registered; however, there have been nomenclature and classification changes, and an increase of known species since the last publication. Objective: To prepare an updated catalog of the vascular plants of Isla del Coco. Methods: The catalog present here is based on the review of herbarium specimens, publications, and plants collected between 2016 and 2017 by the authors. An updated list of plants on the island was prepared. In addition, the estimated richness and the quality of the inventory were determined through biodiversity estimators and the proportion of species according to their form, epiphytic habitat, and origin. Results: 296 species of vascular plants were registered, corresponding to 199 genera and 82 families, which represents about 80% of the expected diversity according to the estimators used (Chao-1 and Clench equation). Of the total, 219 (74%) species are native and 77 (26%) are introduced. Native species include angiosperms (53%), ferns (44%) and lycophytes (3%), and those introduced are represented only by angiosperms. The most diverse families and genera and the most common or abundant species are indicated. From the native flora, 48 spp. (22%) are endemic, and is mainly composed of ferns (58%). The flora has a high proportion of herbaceous species (63%) and a low representation of arborescent species (12%) and vines (8%). There is also a high proportion of epiphytes (20% of the total flora), mostly composed of ferns (69%). This study added 45 new species records to the island, of which 16 are new species for science and endemic to the island, and eight are introduced species. Thirty-six species names were updated or corrected compared to Trusty et al. (2006). A catalog of species with annotations is provided. Conclusions: The flora of Isla del Coco presents certain peculiarities that distinguish it from other Pacific oceanic islands, especially due to the high proportion of endemic ferns, and the high diversity of this group in general, and the relatively low percentage of endemism. Also, characteristics as the low diversity of tree species, with high dominance of Sacoglottis holdridgei in all the forests of the island, and the high proportion of epiphytic species, mainly composed of ferns. The proportion of introduced species is relatively low, compared to other oceanic Pacific islands.